1962
DOI: 10.1097/00000658-196201000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Portal Hypertension According to State of Intrahepatic Circulation

Abstract: IN-portal hypertension, symptoms may vary from case to case; some patients will show ascites only, while others will have esophageal varices and splenomegaly. We were interested in the cause of these variations and, particularly, in ascertaining the best surgical treatment for this condition. The present paper is a review of our own surgical experience and laboratory studies in portal hypertension and a discussion of methods used by others.We have investigated 205 surgical cases with portal hypertension which,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1965
1965
2007
2007

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Two large series of patients with portal hypertension in Japan before 1975 [12,13] had shown that about one-third of all patients with portal hypertension could be classified as IPH. Imanaga et al [12] analyzed 205 patients of portal hypertension, surgically treated before 1961 at Nagoya University Hospital and found 70 (31.1%) cases of IPH, while in another series at Kyushu University Hospital [13], there were 225 (29.2%) cases of IPH among 771 cases of portal hypertension in the period . The incidence of IPH appears to have declined in Japan since 1970 [11].…”
Section: Epidemiology Of Iphmentioning
confidence: 99%
“…Two large series of patients with portal hypertension in Japan before 1975 [12,13] had shown that about one-third of all patients with portal hypertension could be classified as IPH. Imanaga et al [12] analyzed 205 patients of portal hypertension, surgically treated before 1961 at Nagoya University Hospital and found 70 (31.1%) cases of IPH, while in another series at Kyushu University Hospital [13], there were 225 (29.2%) cases of IPH among 771 cases of portal hypertension in the period . The incidence of IPH appears to have declined in Japan since 1970 [11].…”
Section: Epidemiology Of Iphmentioning
confidence: 99%
“…The remaining 9 pa tients with TEPG and 6 treated with proxi mal gastric transection with extensive devas cularization and splenectomy (PGT) were rehabilitated to their former occupations without recurrence of esophageal varices. Discussion IPO, the term for intrahepatic portal hy pertension caused by noncirrhotic fibrosis of the liver, was first proposed by the Nagoya group [1]. Although the liver scarring could be attributed to congenital hepatic fibrosis, schistosomiasis, vinyl chloride intoxication, primary biliary cirrhosis, etc.…”
Section: Resultsmentioning
confidence: 99%
“…10 At Kyushu University Hospital, 771 cases of portal hypertension were treated at the Surgical Department in the period of . Of these, 400 were cirrhosis and 225 IPH.…”
mentioning
confidence: 99%